Public Relations Interdisciplinary Teaching at Spanish and Mexican Universities. An exploratory study - Flores Mayorga, Marco Tulio (2011)
This research analyzes the current educational models of Public Relations in Spain and Mexico. It also identifies the subjects of the curriculum designed for the teaching of Public Relations. It uses an exploratory sample of 11 universities with long experience and tradition studies of public relations and communications in Spain and Mexico. The study methodology is based on the content analysis of the training curriculum of undergraduate public relations. The results reveal that public relations in Spanish universities acquire presence (20%). On the other hand, its presence in Mexico is not as strong (14%) and lag behind marketing, economics, business and administration. The interdisciplinary courses represent 80% in Spain and 86% in Mexico. Among these, the presence varies: the social sciences make up 10% in Spanish universities and 14.8% in Mexico, philosophy and literature are the presence of 2% and 0.4% respectively.